2019
DOI: 10.1097/md.0000000000018286
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary function after robotic exoskeleton-assisted over-ground walking training of a patient with an incomplete spinal cord injury

Abstract: Rationale: Spinal cord injury (SCI) patients who experience difficulties with independent walking use gait-assistive devices such as a cane, walker, or wheelchair. Few studies have explored gait patterns or cardiopulmonary function in chronic SCI patients after powered exoskeleton training. We investigated whether the cardiopulmonary function of a patient with an incomplete chronic cervical SCI and a hemiplegic gait pattern could be improved by walking training using a powered exoskeleton (Angelegs).Patient co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 9 publications
1
24
0
Order By: Relevance
“…The design of the selected studies included case series/reports ( n = 7) [ 34 , 35 , 36 , 41 , 42 , 44 , 47 ], pilot studies ( n = 1) [ 28 ], prospective open label ( n = 1) [ 39 ], self-controlled feasibility ( n = 1) [ 31 ], longitudinal cohort ( n = 1) [ 40 ], prospective cohort ( n = 1) [ 38 ], randomised crossover trial ( n = 2) [ 37 , 43 ], open label prospective quasi-experimental ( n = 1) [ 30 ], prospective single group observational ( n = 1) [ 14 ], experimental ( n = 5) [ 22 , 29 , 32 , 33 , 45 ], cross sectional ( n = 1) [ 21 ] and comparative ( n = 1) [ 46 ] studies. The studies were conducted in the USA ( n = 13) [ 14 , 22 , 28 , 32 , 34 , 35 , 37 , 39 , 40 , 41 , 42 , 44 , 45 ], UK ( n = 2) [ 29 , 31 ], Canada ( n = 2) [ 21 , 38 ], Korea ( n = 2) [ 36 , 43 ], Italy ( n = 2) [ 33 , 47 ] and Australia ( n = 1) [ …”
Section: Resultsmentioning
confidence: 99%
“…The design of the selected studies included case series/reports ( n = 7) [ 34 , 35 , 36 , 41 , 42 , 44 , 47 ], pilot studies ( n = 1) [ 28 ], prospective open label ( n = 1) [ 39 ], self-controlled feasibility ( n = 1) [ 31 ], longitudinal cohort ( n = 1) [ 40 ], prospective cohort ( n = 1) [ 38 ], randomised crossover trial ( n = 2) [ 37 , 43 ], open label prospective quasi-experimental ( n = 1) [ 30 ], prospective single group observational ( n = 1) [ 14 ], experimental ( n = 5) [ 22 , 29 , 32 , 33 , 45 ], cross sectional ( n = 1) [ 21 ] and comparative ( n = 1) [ 46 ] studies. The studies were conducted in the USA ( n = 13) [ 14 , 22 , 28 , 32 , 34 , 35 , 37 , 39 , 40 , 41 , 42 , 44 , 45 ], UK ( n = 2) [ 29 , 31 ], Canada ( n = 2) [ 21 , 38 ], Korea ( n = 2) [ 36 , 43 ], Italy ( n = 2) [ 33 , 47 ] and Australia ( n = 1) [ …”
Section: Resultsmentioning
confidence: 99%
“…Some previous studies [23][24][25]35] have shown that robotic exoskeletons provide improvement in VO 2 peak Fig. 2 CONSORT diagram of enrollment of participants into the study among the incomplete SCI individuals during gait training.…”
Section: Exoskeleton-assisted Walking Training Enhanced the Pulmonary Function Parameters Among Individuals With Spinal Cord Injurymentioning
confidence: 99%
“…Despite the potential walking benefits of EAW, there are few studies manifested that used EAW trainings for PF improving. A quantity of studies has manifested the improvements of metabolic responses, such as heart rate and VO 2 max [23][24][25] during the training program. Nevertheless, none of them has focused on the changes of PF parameters by PFT which contained the vital capacity, forced vital capacity (FVC), forced expiratory volume in 1 second (FEV 1 ), forced expiratory flow (FEF 25/50/75 ), peak expiratory flow (PEF), and maximal voluntary ventilation (MVV).…”
Section: Introductionmentioning
confidence: 99%
“…EAW training enhanced the PF parameters among individuals with SCI Some previous studies [22][23][24]33] have shown that robotic exoskeletons provide improvement in VO 2 peak among the incomplete SCI individuals during gait training. We reported changes in PF parameters among complete and incomplete SCI individuals.…”
Section: Discussionmentioning
confidence: 88%
“…Despite the potential walking bene ts of EAW, there are few studies manifested that used EAW trainings for PF improving. A quantity of studies has manifested the improvements of metabolic responses, such as heart rate and VO 2 max [22][23][24] during the training program. Nevertheless, none of them has focused on the changes of PF parameters by pulmonary function test (PFT) which contained the vital capacity, forced vital capacity (FVC), forced expiratory volume in 1 second (FEV 1 ), forced expiratory ow (FEF 25/50/75 ), peak expiratory ow (PEF), and maximal voluntary ventilation (MVV).…”
Section: Introductionmentioning
confidence: 99%